Correlating Selenium Concentrations with Immunological and Blood Biochemical Variations in Rats - Savita, Ritika Mehra, Deepak Mehta (Revista Electronica de Veterinaria, 2024)
In living things, selenium is a trace element which is required for many metabolic activities and also for preserving physiological homeostasis. In this research, we analyses the connections among selenium ranges with immunological and blood biochemical changes in rats. An entire randomized approach was used to split 25female Wistar rats into 5 equal groups based on their mean body weight (BW) of 124.3±3.1 g BW. With the exception of the kind and quantity of selenium (Se) in the nourishment, the experimental feeding was comparable in all groups. Over the course of 70 days, experimental feeding was carried out. Biochemical profiles were investigated in the experimental trial. When compared to the control group, all of the Wistar rats given Se supplementation had a substantial (p<0.001) decrease in their mean blood total cholesterol. Selenium concentrations and the rats' immune responses were shown to be correlated by the results. Moreover, statistical analysis revealed in ANOVA, confirming the notion that selenium levels significantly affect blood biochemical and immunological markers in rats. The highest levels of serum globulin, and enhanced immunological structure were achieved among the female wistar rats when selenium supplemented at a concentration of 75 ppb. Finally, the results of this study shed important light concerning the way of selenium affects rat blood biochemical indicators and immune responses.